The absent minded professor [videorecording (DVD)] - Stevenson, Robert, 1905-1986; MacMurray, Fred, 1908-1991; Olson, Nancy, 1928-; Wynn, Keenan, 1916-1986; Kirk, Tommy; Ames, Leon, 1902-1993 (Distributed by Buena Vista Home Entertainment, 2003)
Classic about a professor that invents an anti-gravity substance he names flubber, that makes inanimate objects and people fly.